Persepsi Kenyamanan Pejalan Kaki pada Jalur Pedestrian Jalan Gajah Mada Denpasar - Wardana, I Made Oddie Gupta; Semarajaya, Cokorda Gede Alit; Mayadewi, Ni Nyoman Ari (Jurnal Arsitektur Lansekap, 2021)
Perceptions of pedestrian convenience on the pedestrian path of Gajah Mada Street Denpasar. Gajah Mada Street as an economic and tourist area requires good and comfortable physical infrastructure to support easy accessibility and circulation of visitors to the area. One of the physical infrastructures is a pedestrian lane which functions as an access to support pedestrian activities. The purpose of this study was to identify the physical conditions of the pedestrian paths and to determine the perception of pedestrian comfort on the pedestrian path at Gajah Mada Street. The research method used in this research is a survey method by performing primary data collection techniques through observation, questionnaires and secondary data through literature study. Based on the research conducted, it is known that there are physical conditions and supporting facilities for the damaged pedestrian paths, in the form of materials and street furniture such as: seats, trash cans and roadside plants. Based on the assessment of perceptional respondents about the condition of pedestrian path has been considered comfortable and safe. The suggestion of this research is that it is necessary to improve the physical condition of the damaged pedestrians. The purpose of improving pedestrian facilities and infrastructure is to facilitate the pedestrians in order to be comfortable and safe in carrying out activities on the pedestrian path.